Type I Interferon-Independent Dendritic Cell Priming and Antitumor T Cell Activation Induced by a Mycoplasma fermentans Lipopeptide - Takeda, Yohei; Azuma, Masahiro; Funami, Kenji; Shime, Hiroaki; Matsumoto, Misako; Seya, Tsukasa (Frontiers in Immunology, 2018)
Mycoplasma fermentans–derived diacylated lipoprotein M161Ag (MALP404) is recognized by human/mouse Toll-like receptor (TLR) 2/TLR6. Short proteolytic products including macrophage-activating lipopeptide 2 (MALP2) have been utilized as antitumor immune-enhancing adjuvants. We have chemically synthesized a short form of MALP2 named MALP2s (S-[2,3-bis(palmitoyloxy)propyl]-CGNNDE). MALP2 and MALP2s provoke natural killer (NK) cell activation in vitro but only poorly induce tumor regression using in vivo mouse models loading NK-sensitive tumors. Here we identified the functional mechanism of MALP2s on dendritic cell (DC)-priming and cytotoxic T lymphocyte (CTL)-dependent tumor eradication using CTL-sensitive tumor-implant models EG7 and B16-OVA. Programmed death ligand-1 (PD-L1) blockade therapy in combination with MALP2s + ovalbumin (OVA) showed a significant additive effect on tumor growth suppression. MALP2s increased co-stimulators CD80/86 and CD40, which were totally MyD88-dependent, with no participation of Toll-IL-1R homology domain-containing adaptor molecule-1 (TICAM-1) or type I interferon signaling in DC priming. MALP2s+OVA consequently augmented proliferation of OVA-specific CTLs in the spleen and at tumor sites. Chemokines and cytolytic factors were upregulated in the tumor. Strikingly, longer duration and reinvigoration of CTLs in spleen and tumors were accomplished by the addition of MALP2s+OVA to -PD-L1 antibody (Ab) therapy compared to -PD-L1 Ab monotherapy. Then, tumors regressed better in the MALP2s/OVA combination than in the -PD-L1 Ab monotherapy. Hence, MALP2s/tumor-associated antigens combined with -PD-L1 Ab is a good therapeutic strategy in some mouse models. Unfortunately, numerous patients are still resistant to PD-1/PD-L1 blockade and good DC-priming adjuvants are desired. Cytokine toxicity by MALP2s remains to be settled, which should be improved by chemical modification in future studies.